Repeat Spinal Anaesthesia for Caesarean section: An Experience at Paropakar Maternity and Women’s Hospital - Pradhan, Ritu; Shrestha, Sangeeta; Gurung, Tara; Shrestha, Amirbabu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study aims to review the haemodynamic effects of the repeat spinal anaesthesia and to identify the different doses of Bupivacaine heavy used for the repeat spinal anaesthesia for the failed spinal in caesarean section. Methods: This study was conducted by reviewing medical anaesthesia records of the cases of the repeat spinal anesthesia regarding any adverse haemodynamic effects. The second dose of bupivacaine heavy, maximum sensory blockade and intraoperative events like bradycardia, hypotension, high spinal, nausea vomiting, conversion to general anaesthesia and inadequate block were also reviewed. Results: Out of 8040 caesarean section under subarachnoid block, 51(0.63%) cases were conducted under repeat spinal anaesthesia from April 2014 to December2016. All the cases had complete spinal failure with no sensory and motor effects even after 10 minutes of the intrathecal injection. The second dose of bupivacaine heavy used was variable but reduced than the first dose. The most common adverse effect was hypotension (27.5%). 50% of cases were uneventful. One case was converted to general anaesthesia even after repeat spinal anaesthesia and 9.8% cases had high spinal above T4. Conclusions: Repeat administration of Bupivacaine heavy in reduced dose and volume can be used in complete failure of administration of first spinal anaesthesia. However, it always requires careful assessment and the judicious monitoring.